Awareness level of Takaful business : a study on UiTM Puncak Alam / Siti Zulaikha Rozak - Rozak, Siti Zulaikha (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Lack of awareness and community knowledge in takaful business has slightly affected the development of takaful products in Malaysia. The main purpose of this thesis is to measure the level of awareness among students at the top of nature in the takaful business. Furthermore, the ancillary purpose of this thesis is to measure their level of understanding and knowledge in takaful business in malaysia. Besides it also to investigate the advantages of takaful system and its schemes offered, to identify factors that can influence students to choose takaful policies and to discover the differences of takaful concept and conventional insurance concept. Thus, there are two methods that have been used in this thesis to achieve each objective ie quantitative methods and methods of study through relevant scientific books, research journals and so forth. The main findings in this study are the level of awareness of takaful business among students at the UiTM Puncak Alam is at a very high level and they also know about Takaful products available in Malaysia. However, their level of awareness of the needs of takaful products in life is still moderate. this is because most of them are more familiar with the conventional insurance system introduced earlier in Malaysia than in the takaful system. Hence, most students also have very high knowledge in takaful business and takaful policy.